Interpreting the Gospel of John : a practical guide - Burge, Gary M., 1952- (2013)
"This tried and true classroom favorite by respected New Testament scholar Gary Burge has been praised for its usefulness. The expanded second edition has been revised throughout to take account of current scholarship and introduces software tools that have become available since the original edition was published. Combining original insight with how-to guidance, this textbook helps students interpret the Gospel of John and apply it in teaching and preaching" -- Publisher description.
Before you begin -- History of interpretation -- Who wrote the Gospel of John? -- How the fourth gospel was built -- Johannine style -- Strategies for interpretation -- The text -- The literary context -- Building a bibliography -- The cultural context -- Word studies in John, Part 1 : word searches -- Word studies in John, Part 2 : word meanings -- Preaching and teaching from the fourth gospel -- The problem of horizons -- Preaching from John -- Commentaries.
Includes bibliographical references and index.
Keywords: Bible. -- Criticism, interpretation, etc